2005
DOI: 10.1210/en.2004-1181
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Small Bowel in the Regulation of Circulating Ghrelin Levels and Food Intake in the Obese Zucker Rat

Abstract: Circulating levels of ghrelin, a stomach peptide that promotes food intake, rise before and fall after meal. We aimed to investigate whether there is an independent contribution of the small bowel to the regulation of ghrelin and appetite. A duodenal-jejunal bypass (DJB) with preservation of normal gastric volume and exposure to nutrients was performed in 12-wk-old obese Zucker ZDF fa/fa rat. Food intake, weight gain, 48-h fasting, and 24-h refeeding levels of total and acylated ghrelin were measured. The DJB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 43 publications
4
48
0
6
Order By: Relevance
“…Studies in rodents have shown that DJB improves diabetes both in obese (Zucker fa/fa rats) (19) and lean (GK rats) (6) type 2 diabetic animals, consistent with several clinical observations of diabetes remission when RYGB or BPD are performed in moderately obese (11,12) or even lean patients (13). On the other hand, other parameters may better define both the risk from diabetes and the diabetes-related outcomes of surgery.…”
Section: Is Type 2 Diabetes An Operable Intestinal Disease?supporting
confidence: 81%
“…Studies in rodents have shown that DJB improves diabetes both in obese (Zucker fa/fa rats) (19) and lean (GK rats) (6) type 2 diabetic animals, consistent with several clinical observations of diabetes remission when RYGB or BPD are performed in moderately obese (11,12) or even lean patients (13). On the other hand, other parameters may better define both the risk from diabetes and the diabetes-related outcomes of surgery.…”
Section: Is Type 2 Diabetes An Operable Intestinal Disease?supporting
confidence: 81%
“…Similar observations have subsequently been made with independent investigations of non-obese diabetic Goto-Kakizaki rats 20,21 and obese diabetic Zucker rats. 18 Likewise, several small, ongoing human studies of DJB all show improvements in glycemic control, including among non-obese patients, with little or no weight loss (Cohen et al 46 and personal communications with Arguelles-Sarmiento J et al, Lakdawala M et al, and Ramos AC et al).…”
Section: The Upper Intestinal Hypothesismentioning
confidence: 99%
“…Consistent with this concept, experimental studies indicate that variations of RYGB improve T2DM not only in obese but also in nonobese diabetic animals. [18][19][20][21] Despite a growing interest in using RYGB to treat T2DM, even among less obese or non-obese patients, the underlying mechanisms of action of this procedure have not been fully evaluated. As gastrointestinal (GI) surgery appears to eliminate T2DM more effectively, rapidly and durably than any existing non-surgical method, and because the usage of bariatric surgery is rapidly increasing worldwide, elucidating the mechanisms by which these operations improve glycemia is an important research priority.…”
Section: Remission Of Diabetes After Rygbmentioning
confidence: 99%
“…Although diabetes can sometimes be controlled through diet and exercise or by pharmaceutical intervention, bariatric surgery offers a permanent solution, precedent to significant weight loss [39,40] for reasons that remain the subject of investigation [41][42][43]. Irrespective of the reason that bariatric surgery works, its economic value can be seen from the preceding analysis of one of obesity's comorbidities.…”
Section: The Economic Impact Of Type 2 Diabetes Mellitusmentioning
confidence: 99%